2014
DOI: 10.1371/journal.pone.0102584
|View full text |Cite
|
Sign up to set email alerts
|

Host Cytokine Responses Induced after Overnight Stimulation with Novel M. tuberculosis Infection Phase-Dependent Antigens Show Promise as Diagnostic Candidates for TB Disease

Abstract: BackgroundWe previously identified Mycobacterium tuberculosis (M.tb) antigen-induced host markers that showed promise as TB diagnostic candidates in 7-day whole blood culture supernatants. The aim of the present study was to evaluate the utility of these markers further, and cross-compare results with short-term antigen stimulated and unstimulated culture supernatants.MethodsWe recruited 15 culture confirmed TB cases and 15 non-TB cases from a high-TB endemic community in Cape Town, South Africa into a pilot c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…For comparative purposes we also included ten additional Mtb antigens identified previously (Rv0867, Rv1009, Rv1733, Rv1737, Rv2029, Rv2032, Rv2034, Rv2389, Rv2450, and Rv3353)2324414748495051525354. Diluted whole blood samples were stimulated for six days and the cytokine levels were assessed by a seven-plex assay (data shown only for IFN-γ, IL-17, TNF-α and IP-10 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For comparative purposes we also included ten additional Mtb antigens identified previously (Rv0867, Rv1009, Rv1733, Rv1737, Rv2029, Rv2032, Rv2034, Rv2389, Rv2450, and Rv3353)2324414748495051525354. Diluted whole blood samples were stimulated for six days and the cytokine levels were assessed by a seven-plex assay (data shown only for IFN-γ, IL-17, TNF-α and IP-10 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The reconstituted antigens were then diluted in sterile 1Â PBS, mixed with undiluted whole blood from each study participant at a final concentration of 10 mg/ml, and incubated overnight (20e24 h) in 24-well tissue culture plates (Corning Ò Corstar Ò , Sigma) as previously described. 18 Sterile 1Â PBS (Lonza, Cat #: 17-517Q) was used as the negative control.…”
Section: Whole Blood Culture Assay (Wba)mentioning
confidence: 99%
“…In a follow up to these studies, we evaluated the potential of some of these promising antigens to elicit a host response in a short term (overnight) whole blood assay compared to the long term (7-day) whole blood assay. 18 This study also evaluated the accuracy of some of these previously reported novel candidate antigens but in a larger study employing a short term (overnight), more field-friendly whole blood assay.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the following methods are currently being used to search fornew TB biomarkers: cytokine array analyses of the sera from patients with active or latent TB infections compared to those from healthy individuals (Weiner et al, 2012;Liu et al, 2013); microarray analyses of the supernatants of centrifuged peripheral blood after stimulation with TB-specific antigens from patients with active or latent TB infections compared to that from healthy individuals (Frahm et al, 2011;Kellar et al, 2011;Murthy et al, 2011;Borgstrom et al, 2012;Skogstrand et al, 2012;Anbarasu et al, 2013;Armand et al, 2014;Essone et al, 2014); and extraction and culture of leukocytes from the peripheral blood of patients with active or latent TB infection and healthy individuals, followed by analysis of the differences insecreted cytokines before and after stimulation with TB-specific antigens (Rivera-Ordaz et al, 2012). However, consistent results have not been obtained using the aforementioned methods because the number of cytokines analyzed is often small and the types of assays usedto detect them vary between studies; thus, a more systematic approach for analyzing all cytokines is needed.…”
Section: Introductionmentioning
confidence: 99%